A neglected tenet of achievement goal theory: Associations between life aspirations and achievement goal orientations. (1st May 2019) - Janke, Stefan; Dickhäuser, Oliver
Abstract: In this article, we propose a hierarchical model of human goal striving. This conceptual model is based in the assumption that broader life aspirations shape achievement goal orientations. Building on Self-Determination Theory, we assumed that intrinsic life aspirations (striving for self-actualization and personal growth) predict learning goal orientations and that extrinsic life aspirations (striving for fame, wealth, and recognition) predict performance goal orientations. We found empirical support for the hypothesized associations within a first set of studies in three achievement related contexts ( n Study1a = 313 university students; n Study1b = 294 teachers; n Study1c = 209 soccer players). This study set provided critical evidence on the robustness of the postulated associations as well as their generalizability to a broad set of contexts. In a final longitudinal study, we investigated the direction of these relationships in a sample of 97 freshmen, who we questioned at the very beginning of their first semester and three months later. Cross-lagged panel analyses support the assumption that initial intrinsic life aspirations positively influence the development of a learning goal orientation in this critical transition period. The overall result pattern indicates that life aspirations are part of the foundation of achievement goal orientations. Highlights: We propose a goal model that connects different tiers of human goal striving. Intrinsic life aspirations should facilitate a learning goal orientation. Extrinsic life aspirations should facilitate performance goal orientations. We find empirical evidence for our model in three different contexts. A longitudinal study partially supports the assumed direction of the relationships.